Phenotypic and Genotypic Variability in Cercospora kikuchii Isolates from Santa Fe Province, Argentina - Rapela, María G. Latorre; Colombini, Mauro A.; González, Ana M.; Vaira, Stella M.; Maumary, Roxana; Mattio, Mónica C.; Carrera, Elena; Lura, María C. (IntechOpen, 2011)
None